#TITLE_ALTERNATIVE# - IRSAMUKTI (NIM 10205058), ROBI
Distribution of temperature, pressure, and entalphy are very important factors in geothermal reservoir characterization. This is because these parameters express the amount of thermal energy contained in the reservoir. In this final project, the reservoir is assumed to be in a liquid state in a porous media and can be stated as a mathematical model using the Darcy Law, the Law of Conservation of Mass, and the Law of Conservation of Energy. This final project aims to calculate the distribution of temperature, pressure, and enthalpy of the geothermal reservoir using a numeric model that can be computed with programming language, in this case MATLAB. The 2D numeric model is built with the finite difference discretization method. The discrete equations built through this method are then solved using the Gauss-Seidel iteration method and the FTCS (forward time center space) method. The simulation results of this final project show the existence of an energy flux supplied continuously from the magma chamber through fracture regions at the base of the reservoir formation causing an increase of enthalpy followed by a rise in temperature throughout the reservoir formation with the highest distribution located in the fracture region. The increase of enthalpy and temperature have the same tendencies, however they do not generally increase linearally with depth. When the value of enthalpy is larger than the enthalpy value of water saturation, the fluids in the reservoir, which were initially in one water state, change into steam or two phases, water-steam.